Question
upstudy study bank question image url

Resuelva \[ \left\{\begin{array}{l}x+2 y=1 \\ 2 x-z=1 \\ 5 y+z=0\end{array}\right. \] indique xyz.

Ask by Coles West. in Peru
Feb 12,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

La solución es \( x = 3 \), \( y = -1 \), \( z = 5 \), y \( xyz = -15 \).

Solution

Solve the system of equations \( x+2y=1;2x-z=1;5y+z=0 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+2y=1\\2x-z=1\\5y+z=0\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=1-2y\\2x-z=1\\5y+z=0\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}2\left(1-2y\right)-z=1\\5y+z=0\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}2-4y-z=1\\5y+z=0\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}z=1-4y\\5y+z=0\end{array}\right.\) - step5: Substitute the value of \(z:\) \(5y+1-4y=0\) - step6: Subtract the terms: \(y+1=0\) - step7: Move the constant to the right side: \(y=0-1\) - step8: Remove 0: \(y=-1\) - step9: Substitute the value of \(y:\) \(z=1-4\left(-1\right)\) - step10: Simplify: \(z=5\) - step11: Substitute the value of \(y:\) \(x=1-2\left(-1\right)\) - step12: Simplify: \(x=3\) - step13: Calculate: \(\left\{ \begin{array}{l}x=3\\y=-1\\z=5\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=3\\y=-1\\z=5\end{array}\right.\) - step15: Rewrite: \(\left(x,y,z\right) = \left(3,-1,5\right)\) La solución de las ecuaciones dadas es \( x = 3 \), \( y = -1 \) y \( z = 5 \). Por lo tanto, \( xyz = 3 \times (-1) \times 5 = -15 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Para resolver el sistema de ecuaciones, comenzamos con las ecuaciones: 1. \( x + 2y = 1 \) (Ecuación 1) 2. \( 2x - z = 1 \) (Ecuación 2) 3. \( 5y + z = 0 \) (Ecuación 3) Primero, despejamos \( z \) en términos de \( y \) usando la Ecuación 3: \[ z = -5y \quad \text{(Ecuación 4)} \] Sustituimos \( z \) en la Ecuación 2: \[ 2x - (-5y) = 1 \Rightarrow 2x + 5y = 1 \quad \text{(Ecuación 5)} \] Ahora tenemos un nuevo sistema con las Ecuaciones 1 y 5: 1. \( x + 2y = 1 \) (Ecuación 1) 2. \( 2x + 5y = 1 \) (Ecuación 5) Multiplicamos la Ecuación 1 por 2 para facilitar la eliminación: \[ 2x + 4y = 2 \quad \text{(Ecuación 6)} \] Restamos la Ecuación 5 de la Ecuación 6: \[ (2x + 4y) - (2x + 5y) = 2 - 1 \] Esto simplifica a: \[ 4y - 5y = 1 \Rightarrow -y = 1 \Rightarrow y = -1 \] Sustituyendo \( y = -1 \) en la Ecuación 1: \[ x + 2(-1) = 1 \Rightarrow x - 2 = 1 \Rightarrow x = 3 \] Ahora usamos el valor de \( y \) en la Ecuación 4 para encontrar \( z \): \[ z = -5(-1) = 5 \] Por lo tanto, los valores son: \[ x = 3, \quad y = -1, \quad z = 5 \] Finalmente, multiplicamos \( x, y, z \) para obtener \( xyz \): \[ xyz = 3 \cdot (-1) \cdot 5 = -15 \] La respuesta es: \[ xyz = -15 \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy